Stem cell-paved biobridge facilitates neural repair in traumatic brain injury - Tajiri, Naoki; Duncan, Kelsey; Antoine, Alesia; Pabon, Mibel; Acosta, Sandra A.; de la Pena, Ike; Hernadez-Ontiveros, Diana G.; Shinozuka, Kazutaka; Ishikawa, Hiroto; Kaneko, Yuji; Yankee, Ernest; McGrogan, Michael; et al. (Frontiers in Systems Neuroscience, 2014)
Modified mesenchymal stromal cells (MSCs) display a unique mechanism of action during the repair phase of traumatic brain injury by exhibiting the ability to build a biobridge between the neurogenic niche and the site of injury. Immunohistochemistry and laser capture assay have visualized this biobridge in the area between the neurogenic subventricular zone and the injured cortex. This biobridge expresses high levels of extracellular matrixmetalloproteinases (MMPs), which are initially co-localized with a stream of transplanted MSCs, but later this region contains only few to non-detectable grafts and becomes overgrown by newly recruited host cells. We have reported that long-distance migration of host cells from the neurogenic niche to the injured brain site can be attained via these transplanted stem cell-paved biobridges, which serve as a key regenerative process for the initiation of endogenous repair mechanisms. Thus far the two major schools of discipline in stem cell repair mechanisms support the idea of “cell replacement” and the bystander effects of “trophic factor secretion.” Our novel observation of stem cell-paved biobridges as pathways for directed migration of host cells from neurogenic niche towards the injured brain site adds another mode of action underlying stem cell therapy. More in-depth investigations on graft-host interaction will likely aid translational research focused on advancing this stem cell-paved biobridge from its current place, as an equally potent repair mechanism as cell replacement and trophic factor secretion, into a new treatment strategy for traumatic brain injury and other neurological disorders.